Loading-Rate Dependence of Rocks in Postfailure Region under Triaxial Compression - Yang Tang; Seisuke Okubo; Jiang Xu; Hailong Zhang; Shoujian Peng (Advances in Materials Science and Engineering)
To study the loading-rate dependence of four types of rocks in the peak and postfailure regions, the alternative strain rate test method is employed in conducting triaxial compressive tests under different confining pressure and moisture conditions. An index of the loading-rate dependence in the postfailure region is proposed, and the effects of confining pressure and moisture condition on the index are analyzed. The reliability of the test results is verified by comparing the experimental and calculated results of stress relaxation. Following are the results. (1) The peak strength and postfailure behavior significantly depend on the loading rate. The indices (nc and nd) of the loading-rate dependence in the postfailure region obtained based on the elastic and unloading moduli show a good linear relationship. It is feasible to use nc to evaluate the loading-rate dependence of rocks in the postfailure region. (2) The loading-rate dependence of the rock strength increases with the increase in the confining pressure. The effect of confining pressure on the loading-rate dependence in the postfailure region is related to the moisture condition state. (3) Water-saturation treatment will increase the loading-rate dependence in the peak and postfailure regions, and the effect of water is greater than that of the confining pressure. (4) The experimental and calculated results of stress relaxation in the postfailure region are in good agreement, thus validating the experimental results.